Zu einigen Stellen in Plautus' Miles - Stockert, Walter (Wiener Studien, 2021)
In this paper I will discuss four passages in the Miles gloriosus whose text isdisputed: Mil. 61-63 contains an unsolved riddle, 93 a corrupt verb, 115 an unusual colloquialexpression, and 450f. an indubitably corrupt noun. In this contribution I want to disencumberthe apparatus criticus of my edition of the play, which will appear in the editiones Sarsinates(Sarsina-Urbino).